Penerapan Model Cooperative Script untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP/MTs - Sundari, Titin; Hafriani, Hafriani; Salasiyah, Cut Intan (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2026)
The purpose of this research was to find out the mathematical communication skills of students who were taught with better Cooperative Script learning models on set operation material in SMP Negeri 1 Labuhanhaji Barat. The research method used was a quasi experimental design. Sampling was done using random sampling. Population in this study all students of class VII SMP Negeri 1 Labuhanhaji Barat. In this study consisted of two classes, namely class VII.2 as an experimental class and class VII.1 as a control class. The data were collected using a mathematical communication ability test sheet which was then analyzed using the independent sample t-test. The results showed that based one the t-test obtained t_count=2,66 and t_table =1,67. Because t_count>t_table then H_0 is rejected and H_1 is accepted so that it can be concluded that the mathematical communication skills of students taught with more Cooperetive Script learning models better than students who were taught with conventional learning models on set operation material in SMP Negeri 1 Labuhanhaji Barat.